Electrochemical Sensing Characteristics of 3D TiO2 Nanostructures with Different Crystal Structures and Morphologies. Issue 14 (1st January 2018) - Bai, Xue; Gao, Kai; Huang, Xin; Qin, Caidie; Zhang, Yi; Han, Xuan
Abstract : Three-dimensional (3D) metal inorganics have gained tremendous interests for a series of applications. Here, we prepared TiO2 microspheres, urchin-like TiO2, and flower-like TiO2 by hydrothermal method. The morphologies of the three 3D TiO2 nanostructures were characterized by scanning electron microscopy and X-ray diffraction analyses. The electrochemical behaviors of the 3D TiO2 nanostructures were investigated by electrochemical impedance spectroscopy and cyclic voltammetry studies. Results showed that 3D TiO2 -modified electrodes exhibited improved electrochemical performance compared with bare electrode. The three 3D nanostructures were then used with a modified glassy carbon electrode to detect dopamine (DA). According to the experimental results, the flower-like TiO2 /GCE demonstrated excellent electrochemical performance than the two other electrodes. The enhanced electrochemical performance of the 3D flower-like TiO2 /GCE is mainly affected by the structure of anatase crystal, which is the most important factor for the enhanced electrochemical performances toward DA detection. The flower-like TiO2 /GCE, urchin-like TiO2 /GCE, and TiO2 microspheres/GCE possessed linear ranges of 0.02–160, 1–180, and 1–160 μM, with limit of detection values of 0.007, 0.31, and 0.33 μM, respectively.